Antimalarial chloroquine indicated for viral infections: myth ou hope? (Research, Society and Development, 2021)
Aim: this article describes the use of chloroquine as an antimalarial agent with potential antivirotic indications for COVID-19 infections. Methods: On line searches and gray literature have been used in the construction of this articles, whose database include PUBMED Central, BVS/BIREME, Web of Science, Science Direct, Higher Level Personnel Improvement Coordinator (CAPES), Periodic Door (Portal de Periódicos da CAPES, The Cochrane Library and PROSPERO). Results: chloroquine and hydroxychloroquine has shown appropriate clinical reports when associated with the antibiotic Azithromycin. It has been authorized for the clinical treatment of grave acute forms of COVID infections by countries like Brazil and USA. Conclusions: Chloroquine seems to have potential antivirotic properties that may be useful in the treatment of the grave acute forms of COVID-19 associated with Azithromycin. Nevertheless, Its indication must include ECG monitoring due to the risk of cardiac QT prolongation able to cause sudden deaths.